The Impact of Political Factionalism on Diplomacy: A Comparative Analysis - Thapa, Santa Bahadur (Darul Yasin Al Sys, 2025)
This study investigates the joint effects of factionalism within opposition groups and states on state strategies in diplomatic negotiations, focusing on how alignments across factional lines influence both internal cohesion and bargaining dynamics at the peace table. The theoretical framework posits that a state’s similarity to its regime and opposition factions significantly shapes negotiation outcomes, including the initiation, nature, and durability of peace agreements. The analysis advances three key propositions: first, states are more likely to engage in symbolic rather than substantive negotiations when their regimes align with at least one opposition faction; second, greater convergence of interests between regime and opposition factions increases the likelihood of reaching peace agreements; and third, conflicts marked by such similarity are more likely to result in compliance with agreements compared to cases without such alignment. Employing a comparative case study methodology, the research examines historical civil conflicts including the Salvadoran Civil War, the Nicaraguan Contra insurgency, the Guatemalan Civil War, the Honduran Contra War, and Algeria’s civil conflict. The findings demonstrate that regime–opposition similarity exerts a stronger influence on negotiation dynamics, agreement formation, and compliance than opposition similarity with third-party actors, offering new insights into the political mechanics of conflict resolution.